Determination of Irrigation Performance Indices for Paddy Cultivation - Abdul Mumin, Mohammad Sham (1999)
Evaluation and monitoring of paddy irrigation schemes (field plot level) traditionally use conventional indices, namely, Relative Water Supply (RWS) and Water Use Efficiency (WUE). Where continuous irrigation was practice, low WUE and high RWS were obtained giving the impression that little water management had been carried out. This is partly blamed on the incorrect use of these indices because the aim of the agency is different from those for which RWS and WUE were developed. A study at field plot level was conducted in Bagan Serai, Perak for one main season to measure the components of water balance in an irrigated paddy field. The components of the water balance were individually measured using a range of equipment. Observations were made to find indicators that can show the performance of water management according to the aim of the agency. These indicators were incorporated in the proposed indices. Plot Consumption Index (PCI) and Effective Water Use Index (EWUI) were developed and proposed to evaluate and monitor the irrigation performance at field plot level. These indices were developed in line with the aim of the agency and that was to maintain the 'Design Water Depth' (DWD) in the field. DWD is the depth of water that should be maintain throughout the planting season. Results of the components of the water balance were used to calculate WUE, RWS, PCI and EWUI. For most of the season, daily values of EWUI were less than 1 but more than 0, indicating that excess water was supplied. Some days recorded negatives values ranging from -0.1 to -6.9. On these days there was heavy rains and the field was flooded. On the weekly basis, week two had a value of 0.32 while week six had a value of 0.16, while the weekly basis, week tw had a value of 0.32 while week six had a value of 0.16, while the last week recorded 2.71 , indicating under supply, a situation commensurate with the end of season. All other weeks indicated excess or flood conditions by its negative values.